Effectiveness of fit testing versus fit checking for healthcare workers respiratory protective equipment: A systematic review - Charlotte Goko; Elizabeth Forster; Matthew Mason; Peta-Anne Zimmerman (Elsevier, 2023)
Objectives: Respiratory protection is critical in healthcare to minimise the risk of airborne infections for healthcare workers (HCWs). It emphasizes the use of proper fitting of particulate filter respirators and equivalent respiratory protective equipment (RPE) to ensure a good facial seal. The systematic review aimed to compare the effectiveness of fit testing and fit checking for HCWs' respiratory protective equipment. Methods: A systematic review of the literature exploring RPE for HCWs to determine the effectiveness of fit-testing versus fit-checking from January 2003 to April 2022 was identified using CINAHL Complete via EBSCO Host, Cochrane Library, EMBASE, PubMed, and MEDLINE via Ovid electronic databases, and grey literature. The study protocol was registered with PROSPERO (registration number: CRD42020213968). Results: Of the 561 articles identified in the search, 25 articles (22 quantitative studies and three guidelines) were included in this review. Overall, these studies suggest fit-testing as a method that is more effective, widely adopted, and reliable in assessing the effectiveness of RPE; however, a respiratory program should include both fit-testing and fit-checking to maximise effectiveness of the RPE. The COVID-19 epidemic highlighted a lack of knowledge among HCWs regarding fit-checking and fit-testing, and relevant education increased the effectiveness of respiratory equipment protection. Conclusion: It is imperative that both fit-testing and fit-checking is implemented in order to ensure HCW safety. It is recommended to integrate education, fit-testing and fit-checking into a comprehensive respiratory protective program run by trained fit-testers. There is also a need for practical testing methods that incorporate the clinical environment.